Beyond Argument Essaying as a Practice of (Ex)Change - Allen, Sarah; Open Textbook Library (Open Textbook Library, 2015)
Beyond Argument offers an in-depth examination of how current ways of thinking about the writer-page relation in personal essays can be reconceived according to practices in the care of the self - an ethic by which writers such as Seneca, Montaigne, and Nietzsche lived. This approach promises to reinvigorate the form and address many of the concerns expressed by essay scholars and writers regarding the lack of rigorous exploration we see in our students' personal essays - and sometimes, even, in our own. In pursuing this approach, Sarah Allen presents a version of subjectivity that enables productive debate in the essay, among essays, and beyond.
Front Matter -- Acknowledgements -- Introduction -- Chapter One: Meeting the Real Self in the Essay -- Chapter Two: Meeting the Constructed Self in the Essay -- Chapter Three: Cultivating a Self in the Essay -- Chapter Four: Imitation as Meditation -- Chapter Five: Self Writing in the Classroom -- Works Cited
In English.
Description based on print resource
Keywords: Humanities -- Textbooks; Rhetoric -- Textbooks